Preoperative physiotherapy in subjects with idiopathic pulmonary fibrosis qualified for lung transplantation: implications on hospital length of stay and clinical outcomes - Polastri, Massimiliano; Dell’Amore, Andrea; Zagnoni, Giulia; Nava, Stefano (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: Lung transplantation (LTx) candidates with chronic disease are more prone to exercise limitations. Preoperative physiotherapy (PP) can improve exercise tolerance, which in some patients, is severely impaired, often leaving them housebound. The aim of this study was to answer this question: In patients with idiopathic pulmonary fibrosis (IPF) qualifying for LTx, is PP effective in improving postoperative outcomes and reducing length of stay (LOS) after transplantation? Methods: Six major databases were searched up to December 2015. We did not apply limits to publication date, date, gender, or language. Citations were accepted if they discussed preoperative physiotherapeutic treatment in patients with IPF waiting for LTx. Results: After the full texts were read, three papers met the inclusion criteria and were included. All of these papers had an observational design. In total, 55 subjects with IPF and awaiting LTx were observed. Conclusions: The effectiveness of PP in improving postoperative outcomes and reducing LOS following LTx remains unclear, although it appears to benefit IPF patients who qualify for LTx by improving their health status, physical activity levels, and respiratory-related symptoms.